RIVER: A RELIABLE INTER-VEHICULAR ROUTING PROTOCOL FOR VEHICULAR ADHOC NETWORKS (International Journal of Engineering and Computer Science, 2017)
Vehicular Adhoc Networks (VANETs), associate degree rising technology, would permit vehicles on roads to make a self-organized network while not the help of a permanent infrastructure. As a requirement to communication in VANETs, associate degree economical route between act nodes within the network should be established, and therefore the routing protocol should adapt to the quickly changing topology of vehicles in motion. This is often one in every of the goals of VANET routing protocols. In this paper, we have a tendency to gift associate degree economical routing protocol for VANETs, referred to as the Reliable Inter-Vehicular Routing (RIVER) protocol. Stream utilizes associate degree aimless graph that represents the surrounding street layout wherever the vertices of the graph ar points at that streets curve or run across, and therefore the graph edges represent the road segments between those vertices. In contrast to existing protocols, stream performs time period, active traffic observation and uses these information and different information gathered through passive mechanisms to assign a reliability rating to every street edge. The protocol then uses these responsibility ratings to select the foremost reliable route. Management messages ar accustomed determine a node’s neighbors; determine the responsibility of street edges, and to share street edge responsibility info with different nodes